Mecanismos de regulación internacional de productos básicos - Villagrán Kramer, Francisco (Estudios Internacionales, 1973)
The negotiations that give rise to the commercialization of basic products at the international level reveal the complexity of such process and a marked trend towards a product-by-product regulation that pits countries against each other. It is therefore important to specify the great variations that occur at the international level with respect to the regulation of basic products, their specific marketing modalities and the incidence of such regimes in the national development programs, and the alignment policies of the countries of the Third World. Reducing the spectrum of our analysis to the merely institutional field would imply being limited to the study of conventional instruments that regulate certain basic products. Hence, the spectrum is broadened, locating the problem within an economic, political and legal context, placing ourselves, consequently, in the real context in which the phenomena occur.